Digital Reformatting and Data Rescue with RADD and the PROUD and PRAVDA Kits - Salo, Dorothea; Hocking, Jesse (KULA, 2018)
Despite the short remaining time to rescue unique cultural and personal materials stored on many twentieth- and early twenty-first-century audiovisual and digital storage media, realistic rescue options are starkly limited. Building a rescue apparatus in house, especially to archival standards, requires significant expertise and expense and is often of limited continuing use. Outsourcing digital capture of these materials overwhelms the resources of even well-funded academic libraries and archives, never mind public libraries, small archives, and local historical societies. To address this problem realistically, the University of Wisconsin-Madison Information School has built and documented an in-house rescue installation called RADD (Recover Analog and Digital Data) as well as two self-contained, portable, and shippable rescue kits: PROUD (Portable Recovery of Unique Data) for digital materials and PRAVDA (Portably Reformat Audio and Video to Digital from Analog) for audio and video. All three units are actively rescuing cultural heritage materials, as well as serving training and outreach functions.